2021
DOI: 10.1021/acssuschemeng.1c02188
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective NADH Regeneration: the Synergy Effect of TiOx and Pt in NAD+ Hydrogenation

Abstract: The regeneration of the reduced form cofactor nicotinamide adenine dinucleotide (NADH) by NAD + hydrogenation is an economical way for the practical application of biocatalysis but still remains a big challenge due to the low selectivity. Herein, we report that the selectivity to NADH could be greatly promoted by the strong metal−support interaction effect between Pt and TiO 2 . It was found that NADH selectivity determined by enzyme analysis increased with Pt/TiO 2 reduction temperature increasing and reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…It was found that the catalyst doped with the lowest amount of Sn (Pt90) gave rise to the highest selectivity to 1,4-NADH, achieving 90%. This is a significant improvement on the previously reported heterogeneous catalysts (which attained a maximum selectivity of 63% 27 ). The improved selectivity can be attributed to directing the adsorption mode of NAD + by disturbing the Pt ensemble.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It was found that the catalyst doped with the lowest amount of Sn (Pt90) gave rise to the highest selectivity to 1,4-NADH, achieving 90%. This is a significant improvement on the previously reported heterogeneous catalysts (which attained a maximum selectivity of 63% 27 ). The improved selectivity can be attributed to directing the adsorption mode of NAD + by disturbing the Pt ensemble.…”
Section: Discussionmentioning
confidence: 46%
“…17,26 Recently, Yang et al assessed a group of Pt/TiO 2 catalysts in H 2 and achieved a selectivity (and yield) of 63%. 27 To date, supported metal catalysts have failed to deliver any further improvements in selectivity/yield. To overcome this, Vincent et al have borrowed the natural performance of enzymes and used a commercial Pd/C (and carbon) to adsorb NAD + reductase, which then exhibits exclusive selectivity to 1,4-NADH.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the myriad unique properties of graphene-based materials specific to hydrogen storage applications, carbonaceous materials can only achieve high gravimetric storage capacities (up to 7.5 wt %) under cryogenic temperatures and high pressures. , Unfortunately, the hydrogen storage capacities of carbon-based materials under ambient conditions are significantly low (up to 1 wt %) due to their weak physical interactivity. To achieve desirable storage capacities of graphene-based materials, the functionalization of graphene nanomaterials and decorating them with metal atoms are potential solutions. , The decoration of carbonaceous materials with metal nanoparticles (NPs) such as Pd, , Pt, and Ni can absorb hydrogen via the so-called hydrogen spillover and Kubas-type interaction phenomenon. However, the tendency of metal NPs to aggregate on the surfaces of graphene sheets prevents significant hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%